South Africa's Financial Sector Charter : transforming South Africa through black economic empowerment - Rosenthal, Jean W., 1945-; Elias, Jaan; Podolny, Joel M. (Joel Marc); Baron, James N. ([London] : SAGE, 2016)
In 1994, South Africa held its first free elections, marking the peaceful transition from a government controlled by the country's white minority to a multi-party, multi-racial government. The new government, led by Nelson Mandela and the African National Congress (ANC) party, sought to unify South Africa and overcome the country's racist past. Rather than pursue criminal recriminations and retribution for past wrongs, the ANC concentrated on reconciliation, unification and nation building. According to most observers, the ANC's political program led to a strong, forward-looking state, capable of undertaking the significant challenges facing South Africa. This case study examines this topic.
Originally Published in: Rosenthal, J.W., Elias, J., Podolny, J., & Baron, J.N. (2007). South Africa's Financial Sector Charter: Transforming South Africa through Black Economic Empowerment. 07-026. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Power (Social sciences) -- South Africa -- Case studies; Blacks -- South Africa -- Economic conditions -- Case studies; South Africa -- Economic conditions -- 1991- -- Case studies; South Africa -- Politics and government -- 1994- -- Case studies; South Africa -- Race relations -- Case studies